Bases of power and job performance - Chaw, Tee Yin (Universiti Malaysia Sarawak (UNIMAS), 2010)
The purpose of · this study is to investigate whether power bases of supervisors will be influence on job perfonnance. In addition, this study also to investigate whether positional power such as coercive power, reward power and legitimate power and personal power such as expert power, referent power, infonnation power and connection power will have influence on job perfonnance such as administration, knowledge of work, communication, teamwork, decision making, expense management, human resource management, independent action, job knowledge, leadership, managing change and improvement, customer responsiveness, personal appearance, dependability, safety and employees' responsivenes~ This study attempts to detennine if there is a relationship between positional power and personal power and job perfonnance. In addition, this study also investigates significant relationship positional and personal power and job perfonnance. The instrument used is a questionnaire to collect data from a total of 100 respondents through simple random sampling technique. All data are analyzed using Statistical Package for Social Science (SPSS) Windows Version 16.0. The Pearson Correlation and Linear Regression are used to test the seven hypotheses. The Pearson Correlation reported that generally, there are significant relationships between bases of power and job perfonnance this study also finds out that there are no significance between coercive power, legitimate power and expert power with job perfonnance. Employees' perfonnance can be improved if these variables given the appropriate attention by supervisors in an organization.